Pengaruh Kampanye Produk Telepon Cerdas “Hollywood in Your Pocket” Pada Iphone 13 Pro Terhadap Keputusan Beli Konsumen: Survei di Sebuah Kampus di Jakarta Selatan - Fadilah, Ramadan Faqih (Prisani Cendekia Institute, 2023)
In this era of globalization, technology is increasing and developing with the times. Technological advances also have a positive impact on the ease of accessing information digitally. Nowadays, smartphones are very much needed by all individuals. With the sophistication of a smartphone, we can find information, communicate and many other benefits. One of the most well-known smartphone companies today is Apple. At first, Apple started its company with computer production. Apple was founded on April 1, 1976, by Reed University students, namely Steve Jobs and Steve Wozniak. In September 2021, Apple released the iPhone 13 with a new feature that the previous iPhone generations didn't have. This feature is a cinematic mode. Can produce bokeh effects automatically, the cinematic mode feature gives a cinematic impression in the style of Hollywood films.This feature can be used in the camera application, then switch to cinematic mode. All of these features are explained in the “Hollywood in Your Pocket” campaign. This study aims to see the effect of the